OR 2.0 context-aware operating theaters and machine learning in clinical Neuroimaging : second International Workshop, OR 2.0 2019, and second International Workshop, MLCN 2019, held in conjunction with MICCAI 2019, Shenzhen, China, October 13 and 17, 2019, Proceedings /: second International Workshop, OR 2.0 2019, and second International Workshop, MLCN 2019, held in conjunction with MICCAI 2019, Shenzhen, China, October 13 and 17, 2019, Proceedings. (2019) - Unknown
No abstract available